2021
DOI: 10.1002/chem.202100301
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bond Acceptor Propensity of Different Fluorine Atom Types: An Analysis of Experimentally and Computationally Derived Parameters

Abstract: The propensity of organic fluorine acting as a weak hydrogen bond acceptor (HBA) in intermolecular and intramolecular interactions has been the subject of many experimental and theoretical studies often reaching different conclusions. Over the last few years, new and stronger evidences have emerged for the direct involvement of fluorine in weak hydrogen bond (HB) formation. However, not all the fluorine atom types can act as weak HBA. In this work, the differential HBA propensity of various types of fluorine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 91 publications
(201 reference statements)
1
19
0
Order By: Relevance
“…In addition, the improvement in the stability could also be attributed to strong hydrogen bonding (FH) and chelating (formation of chelates between FPb and SOPb) effects. [ 68,70–72 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the improvement in the stability could also be attributed to strong hydrogen bonding (FH) and chelating (formation of chelates between FPb and SOPb) effects. [ 68,70–72 ]…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the improvement in the stability could also be attributed to strong hydrogen bonding (FH) and chelating (formation of chelates between FPb and SOPb) effects. [68,[70][71][72] We calculated the work function, valence band maximum (VBM), and conduction band minimum (CBM) levels for the pristine and HFSTT-modified perovskite films using the ultraviolet photoelectron spectroscopy (UPS, Figure 4a,b) technique to understand the reason behind the increase in the V oc values of the solar cells. Figure 4c presents the energy level diagrams generated based on the data obtained using the UPS and optical absorption techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the insect β subunit plays a decisive role in the recognition of the C­(O)­CF 3 pharmacophore. A fragile H-bond between a fluorine atom and the partnering H-donating amino acid has an important implication for protein-ligand recognition. , Although the organic fluorine atom interacts with a cation such as Na + or K + , a CF 3 fluorine contacts Lys ammonium H or Arg guanidinium H . Further, FLP is acaricidal against various ticks (Table S1), while neonicotinoid IMI is less effective, , which is apparently associated with the fact that the FLP C­(O)­CF 3 moiety interacts with the partnering residue(s) on the tick nAChR β subunit.…”
Section: Discussionmentioning
confidence: 99%
“…This seems reasonable as we inferred earlier that F_ali and F_phe tend to be more electron rich than the others, which should make the F δ-•••C δ+ interaction stronger. On the other hand, an analysis of 19 F chemical shifts suggested that shielded (high electron density) fluorine atoms in proteins are more likely to interact with hydrogen-bond donors and less likely to form F•••CO interactions than deshielded atoms. 130 The authors argued (along with Holl et al 131 ) that if a fluorine atom with high electron density forms an F•••CO contact it will also form a secondary, and repulsive, interaction to the carbonyl oxygen.…”
Section: F•••f Geometriesmentioning
confidence: 99%